Efficacy of an Intrathecal Multidrug Infusion for Pain Control in Older Adults and in End-Stage Malignancies: A Report of Three Cases - Sadegh Abdolmohammadi; Pierre-Olivier Hétu; Andrée Néron; Gilbert Blaise (Pain Research and Management)
The aim of the present study was to explore the effectiveness of an alternative method to manage pain based on a time-limited intrathecal (IT) infusion of an analgesic medication mixture. Three patients (69, 64 and 94 years of age) with intractable and poorly controlled pain due to bed sores, pelvic metastatic mass, and thoracic vertebra and rib fractures, respectively, were treated. Daily doses of opioids could not be increased due to side effects. An IT catheter (20 G) was placed by percutaneous approach in the lumbar area while advancing toward the thoracic region, and was then tunnelled and fixed subcutaneously. It was connected to an external infusion pump with a mixture of bupivacaine 1 mg/mL, naloxone 0.02 ng/mL, ketamine 100 μg/mL, morphine 0.01 mg/mL and clonidine 0.75 μg/mL. The starting rate was 1 mL/h. The pain was mostly controlled at a rate of <1 mL/h. Opioid consumption was reduced dramatically. The catheter was kept in place for one month in the first and third patients, and for six months in the second patient, until his death. Major side effects, such as hypotension, constipation, muscle weakness, sphincter dysfunction, and cognitive or mood deterioration, were not observed with this approach. One patient experienced a urinary tract infection followed by sepsis and meningitis, which was cured by antibiotics. The catheter was removed in this patient. IT infusion with a low-concentration multidrug mixture could be considered as an alternative modality for intractable pain relief in older adults or in malignancies.